2015
DOI: 10.1177/1753193415581517
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of hook plate fixation versus extension block pinning for bony mallet finger: a retrospective comparison study

Abstract: The aim of this retrospective study was to determine whether traumatic mallet fractures had better outcomes when treated by hook plate fixation (13 patients) or extension block pinning (19 patients). We assessed outcomes using Crawford's criteria; distal interphalangeal joint range of motion; the DASH score; and a visual analogue scale score for pain. We measured radiological parameters. No significant differences were observed in functional and clinical outcomes and in complications. Whereas the operative tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 28 publications
(38 reference statements)
5
30
0
9
Order By: Relevance
“…In terms of active DIPJ flexion, our study results were comparable with that in previous studies, which reported mean active flexion of 61° to 73° following extension block pinning, with mean follow up period of 11.9 to 34 months [8,13,16]. Patients in group 1 returned to their full occupational capacity significantly shorter than that in group 2.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In terms of active DIPJ flexion, our study results were comparable with that in previous studies, which reported mean active flexion of 61° to 73° following extension block pinning, with mean follow up period of 11.9 to 34 months [8,13,16]. Patients in group 1 returned to their full occupational capacity significantly shorter than that in group 2.…”
Section: Discussionsupporting
confidence: 87%
“…This significant loss of extension explains the lack of excellent results according to Crawford criteria in group 1 patients. In comparison, all 11 patients in group 2 achieved excellent or good results, which is comparable to the 64 % to 94 % results reported in previous studies [8,[13][14][15].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…There are several surgical techniques in the treatment of mallet finger such as repair using micro-screws, Kirshner wire pinning, and hook-plate, external fixator or button application (11)(12)(13)(14)(15)(16)(17). Surgical treatment has advantages in terms of early postoperative mobilization of fingers and early return to work.…”
Section: Introductionmentioning
confidence: 99%